Immune and Inflammation Markers as a Predictor of Overall Survival in Patients with Hematologic Malignancies: A Retrospective Cohort Study - Mehmet Ali Ucar; Anıl Tombak; Aydın Akdeniz; Hüseyin Derya Dinçyürek; Meryem Şener; Mahmut Bakır Koyuncu; Eyüp Naci Tiftik; Recep Dokuyucu (Medicina, 2025)
Background and Objectives: this study aimed to evaluate the prognostic significance of systemic immune-inflammatory markers, particularly the pan-immune-inflammation value (PIV) and systemic immune-inflammation Index (SII), in predicting overall survival among patients with hematologic malignancies. Materials and Methods: This retrospective cohort study included 300 patients diagnosed with various hematologic malignancies between January 2020 and January 2025 at the Department of Hematology, Faculty of Medicine, Mersin University. Baseline laboratory data, including neutrophil, lymphocyte, platelet, and monocyte counts, were collected to calculate SII, NLR, PLR, and PIV. Patients were stratified into high and low groups based on the median values of these markers. Overall survival was analyzed using Kaplan–Meier curves and Cox proportional hazards models, adjusted for age, sex, malignancy type, and disease stage. Results: High levels of PIV and SII were significantly associated with poorer overall survival. In univariate analysis, high PIV (HR: 2.35, 95% CI: 1.68–3.28, p < 0.001) and high SII (HR: 2.12, 95% CI: 1.53–2.95, p < 0.001) were strong predictors of mortality. After multivariate adjustment, PIV (adjusted HR: 2.14, 95% CI: 1.47–3.11, p < 0.001) and SII (adjusted HR: 1.88, 95% CI: 1.32–2.67, p = 0.001) remained independent prognostic factors. Subgroup analyses demonstrated that the predictive power of PIV and SII was consistent across different malignancy types, particularly in acute myeloid leukemia and multiple myeloma patients. Conclusions: Our findings indicated that systemic immune-inflammatory markers, particularly PIV and SII, are valuable prognostic tools in hematologic malignancies. These markers, derived from routine blood counts, offer a simple cost-effective means for improving risk stratification. Incorporating these indices into clinical practice could enhance individualized management strategies. Further prospective studies are warranted to validate these findings.